Effective representations for road scene understanding with scalable learning - Bruls, TAH (2020)
Autonomous vehicles require an accurate understanding of the scene for safe operation in real-world driving scenarios. This thesis examines and offers effective representations for road scene understanding based on in-situ perception, which can be employed directly for planning and decision making in a variety of complex urban environments and under wide-ranging environmental conditions.